Capital Structure, Investment Growth, and Liquidity Effects on Automotive Companies’ Financial Performance - Riska Mandasari; Brady Rikumahu (LPPM STIE KRAKATAU, 2024)
Purpose: This study analyzes the influence of capital, investment, and liquidity structures on the financial performance of automotive companies and their components listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Methodology: The study used multiple regression analysis with data obtained from annual financial reports. A purposive sampling technique selected 15 automotive companies as the sample. Results: The results show that capital structure has a significantly positive effect on financial performance, while investment and liquidity do not significantly affect financial performance. Conclusions: This study concludes that capital structure significantly improves financial performance, while investment growth and liquidity do not have a significant effect on automotive companies’ performance. Effective capital management is essential for enhancing financial outcomes. Limitation: The study's limitation is that it focuses solely on automotive companies listed on the Indonesia Stock Exchange during the specified timeframe. Contribution: This study provides empirical evidence on financial factors affecting automotive companies’ performance and offers insights for investors, creditors, and financial managers.